Befriending carers of people with dementia: randomised controlled trial. Issue 7656 (27th May 2008) - Charlesworth, Georgina; Shepstone, Lee; Wilson, Edward; Reynolds, Shirley; Mugford, Miranda; Price, David; Harvey, Ian; Poland, Fiona
Abstract : Objective To evaluate the effectiveness of a voluntary sector based befriending scheme in improving psychological wellbeing and quality of life for family carers of people with dementia. Design Single blind randomised controlled trial. Setting Community settings in East Anglia and London. Participants 236 family carers of people with primary progressive dementia. Intervention Contact with a befriender facilitator and offer of match with a trained lay volunteer befriender compared with no befriender facilitator contact; all participants continued to receive "usual care." Main outcome measures Carers' mood (hospital anxiety and depression scale—depression) and health related quality of life (EuroQoL) at 15 months post-randomisation. Results The intention to treat analysis showed no benefit for the intervention "access to a befriender facilitator" on the primary outcome measure or on any of the secondary outcome measures. Conclusions In common with many carers' services, befriending schemes are not taken up by all carers, and providing access to a befriending scheme is not effective in improving wellbeing. Trial registration Current Controlled Trials ISRCTN08130075 .